Integration interrupted : tracking, black students, and acting White after Brown - Tyson, Karolyn (New York ; Oxford : Oxford University Press, 2011)
There is lots of popular and scholarly concern today about why African American students aren't doing better in school. Instead of looking at the students, Tyson argues that when and where students understand race to be connected with achievement, it is a powerful, if indirect, lesson conveyed by schools.
Includes bibliographical references and index.
Description based on print version record.
Keywords: African Americans -- Education; African Americans -- Education -- Social aspects; African American students -- Social conditions; African American students -- Ethnic identity; School integration -- United States; Track system (Education) -- United States; Academic achievement -- United States